Peran Teknologi Analitik Digital untuk Pengambilan Keputusan Strategis bagi Pengusaha UMKM Perempuan di Kota Bandung - Sukardi, Yoki Oktorian; Nurjamilah (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Research aim : Objective of this study is to assess and investigate the impact of digital analytics technology on strategic decision-making, its effect on the business performance of small and medium-sized enterprises (SMEs), and the experiences of female SME entrepreneurs in Bandung regarding the adoption of digital analytics technology through the Technology Acceptance Model (TAM) framework. Design/Methode/Approach : A sequential explanatory mixed-method approach was used, engaging 60 female small and medium-sized enterprise owners in Bandung. Participants were selected via Stratified Random Sampling. Research Finding : This research revealed that, despite the promise of digital analytics technology to enhance strategic decision-making for female MSME owners in Bandung City, opinions of its utility and simplicity of use remain low. A considerable number of respondents perceived that technology did not provide substantial advantages in their company operations and encountered challenges in its use. Theoretical contribution/Originality : Focus of this study is the application of the Technology Acceptance Model (TAM) to strategic decision-making among female small and medium-sized enterprise (SME) entrepreneurs. Practitioner/Policy implication : The study highlights the need for enhanced digital literacy through training programs for female SME entrepreneurs in Bandung and the development of supportive policies to facilitate access to and use of digital analytics technology. Research limitation : The study is limited to female SME entrepreneurs in Bandung.